A Quantıtatıve Study on the Score and Technıcal Analysıs of the 2021 Olympıc Games and 2021 World Champıonshıps Olympıc Weıghts-Men's Freestle Wrestlıng - Rafet Ünver, (Pakistan Journal of Medical & Health Sciences, 2022)
In amateur sports branches, one of the most important and big sports organizations for both athletes, coaches, and also for the countries is the Olympic Games and the other is the World Championships. The Olympic Games, which could not be held in 2020 but postponed to 2021 due to the Covid-19 Pandemic in the world, and the 2021 World Wrestling Championship, which is included in the 2021 activity program of the United World Wrestling (UWW), were held in the same year with very short intervals. However, 72% of the wrestlers who participated in the Olympic Games either could not participate in the World Championship or were replaced with another athlete from the same country. In this study, some competition components and score analyses of the Men's Free Wrestling Competitions held in these two major sports organizations on the basis of Olympic weights were made and their similarities and differences were revealed. While 96 athletes participated in the Olympic Games Men's Freestyle Wrestling competitions in six Olympic weight categories and performed 114 competitions, in the World Championship Men's Freestyle Wrestling, 144 athletes performed 162 competitions in the aforementioned six Olympic weight categories. Average points per competition were 9.18 points at the Olympic Games and 9.62 points at the World Championships. In both championships, the highest number of wins was by points, and their rates were 69% in the Olympic Games, and 61% in the World Championships. In both championships, the finishing times of the competitions were recorded as the highest value in completing the normal time, and their rates were determined as 72% in the Olympic Games and 61% in the World Championships. The average times per competition were determined as 5 minutes 23 seconds in the Olympic Games and 4 minutes and 49 seconds in the World Championships. The frequency of technical points earned was determined as the highest frequency of 2 points in both championships and the average frequency of 2 points per match was 3.32 in the Olympic Games, while it was 3.39 in the World Championships. With these results, no statistically significant difference was observed in terms of the competition components analysed in the Olympic Games and World Championships (p>0.05).